RESIKO MEDIS DAN KELALAIAN MEDIS DALAM ASPEK PERTANGGUNGJAWABAN PIDANA - Ilahi, Wahyu Rizki Kartika (Jurnal Hukum Volkgeist, 2018)
Healthy is very important for every people, keep healthy is very important, if some people ill and must opname when the doctor must get to make medic for some people, but the end of get medic is unsatisfactory result.in the term of unsatisfactory result from get medic, make medical loss for patient and patient’s family, in medical loss result make many issues for doctor. but must know in the fact, not every unsatisfactory result get responsibility.this thesis make a normative yuridis metode with statue approach and conceptualapproach metode. in this thesis discuss about responsibility doctor for medical risks and medical risks which can be account for by doctor